(untitled) (MAUSAM, 1995)
The four major biophysical controls of vegetation which govern land-atmosphere interaction emanate from the ability or vegetation to. (a) evapotranspire (b) trap solar radiation within leaf organizations. (c) regulate evapotranspiration by stomatal control and (d) modify (generally increase) the surface roughness on the scale of turbulent eddies, Simulation studies with General Circulation Models together with a few observational analyses have provided a rational understanding of vegetation-precipitation interaction. In studies with artificially enhanced vegetation-related processes a strong dependence of rainfall on vegetation has been inferred. For Sahelian and other tropical desert-border regions, where evapotranspiration is small, increasing the surface-albedo (desertification) decreases rainfall. When evaportranspiration and or land-surface roughness are increased in some selected regions - a potential effect of vegetation an increase in local rainfall is produced. The above effects both individually and jointly have simulated increased monsoon rainfall over the Indian subcontinent. Modelling studies directed at understanding the relationship between tropical forests and rainfall with realistic models of the biosphere have simulated a warmer and drier climate in response to Amazonian deforestation. Since forests absorb more solar energy and produce much larger evaportranspiration, as well as moisture convergence through the surface-roughness effect, positive feedback effect of forests on precipitation can be expected naturally. Our new simulation experiments not only reaffirmed the above results but also suggested potential global consequences due to the ongoing deforestation. From a synthesis of modeling results of the last decade, it if further inferred that variations in the biosphere-atmospheric interactions play an important role in redistributing continental precipitation to fulfill the survival and growth requirements of different biomes: forests, pasture, agricultural lands, and deserts.